Renal artery coil embolization for management of bleeding in severe renal trauma: a case report - Haris; Kokohana, I Putu (Indonesian Vascular Access Association (IVAA), 2024)
Background: Among genitourinary tract injuries, renal trauma is the most often damaged organ. Renal trauma makes up between 0.3- 3.25 % of all injuries and can cause hemorrhage, damage to the collecting system which could result in urine leakage, or injury to the renal parenchyma or renal vasculature. Clinical stage affects the type of treatment chosen for renal trauma. Grading of renal injury and guiding for treatment and intervention are possible using the AAST grading system. The grades assigned based on renal trauma imaging and clinical features have an impact on the prognosis and treatment plan for the patients. This study aimed to present a renal artery coil embolization in severe renal trauma management. Case presentation: In this report, we describe a 30-year-old man who had a history of a traffic injury an hour prior, along with extensive hematuria and stomach pain. AAST grade V severe renal damage and a sizable hematoma were shown by an abdominal CT scan.To stop the renal bleeding, the patient received endovascular embolization treatment. Four days following the intervention, the patient was released from the hospital without showing any signs of kidney hemorrhage. Conclusion: The minimally invasive technique of endovascular angiography and embolization has demonstrated promising clinical outcomes. This technique can be used to stop bleeding in patients with hemodynamically stable renal injuries and can avoid surgery or nephrectomy in some circumstances.